2008
DOI: 10.3174/ajnr.a1256
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity MR Imaging Reveals Cortical Functional Connectivity in the Developing Brain

Abstract: BACKGROUND AND PURPOSE:Unlike conventional functional MR imaging where external sensory/ cognitive paradigms are needed to specifically activate different regions of the brain, resting functional connectivity MR imaging acquires images in the absence of cognitive demands (a resting condition) and detects brain regions, which are highly temporally correlated. Therefore, resting functional MR imaging is highly suited for the study of brain functional development in pediatric subjects. This study aimed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
179
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(187 citation statements)
references
References 36 publications
8
179
0
Order By: Relevance
“…The high-growth association cortex also exhibits the most protracted course of GM maturation than the low-growth visual and sensorimotor cortices (Gogtay et al, 2004;Shaw et al, 2008). In infants, the resting-state networks are present in the lowgrowth sensorimotor, visual, and auditory cortices (Fransson et al, 2007(Fransson et al, , 2011Lin et al, 2008), whereas the default network involving high-growth inferior parietal, prefrontal, and temporal cortices does not fully develop until 2 years of age . Evolutionary high expansion of cortical surface area between macaque and human is also found in the association cortex, including prefrontal, temporal, and parietal association areas (Hill et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-growth association cortex also exhibits the most protracted course of GM maturation than the low-growth visual and sensorimotor cortices (Gogtay et al, 2004;Shaw et al, 2008). In infants, the resting-state networks are present in the lowgrowth sensorimotor, visual, and auditory cortices (Fransson et al, 2007(Fransson et al, , 2011Lin et al, 2008), whereas the default network involving high-growth inferior parietal, prefrontal, and temporal cortices does not fully develop until 2 years of age . Evolutionary high expansion of cortical surface area between macaque and human is also found in the association cortex, including prefrontal, temporal, and parietal association areas (Hill et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Given the regional variations of the cortical folding, methods for measuring cortical local gyrification have also been proposed (Schaer et al, 2008;Toro et al, 2008;Lebed et al, 2013) to characterize the localized changes of the cortical folding during brain development, aging, and disorders. MR imaging studies have found that global and regional cortical GIs correlate with age (Raznahan et al, 2011), gender (Rogers et al, 2010, and cognitive functions (Luders et al, 2008). However, existing studies of cortical GI development are limited to schoolage children and adolescents (Raznahan et al, 2011;Shaw et al, 2012), whose GIs change little from year to year.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable functional network architecture has been revealed in the neonatal brain, albeit in an immature state (Doria et al, 2010a;Fransson et al, 2009;Gao et al, 2014aGao et al, , 2014bGao et al, , 2013Gao et al, , 2009Lin et al, 2008;Smyser et al, 2010) (Figure 3). Primary networks can be clearly depicted in newborn infants and display a mature configuration whilst higher-order networks are largely fragmented (Doria et al, 2010a;Fransson et al, 2009;Gao et al, 2014aGao et al, , 2014bSmyser et al, 2010).…”
Section: Functional Network Developmentmentioning
confidence: 95%
“…A number of studies have focused on the emergence of resting-state networks in fetuses and newborn infants (Alcauter et al, 2015a;Arichi et al, 2010;Fransson et al, 2009, Gao et al, 2014a, 2014b, 2009Lin et al, 2008;Schöpf et al, 2012;Smyser et al, 2010;Thomason et al, 2015). In healthy adults, a distinct set of resting-state networks has been described encompassing brain regions involved in primary functions (i.e.…”
Section: Functional Network Developmentmentioning
confidence: 99%
“…This is in accordance with network connectivity patterns seen in human (Cordes et al 2001) and monkey (Vincent et al 2007) studies that demonstrated bilateral motor, auditory, and visual networks. In humans, these networks have been shown to be present at birth (Fransson et al 2009;Lin et al 2008). Higher order restingstate networks also exhibit high degrees of synchronization between cortical and subcortical inter-hemispheric homologues (Beckmann et al 2005).…”
Section: Introductionmentioning
confidence: 99%